Pendidikan Transformatif Menuju Masyarakat Demokratis - Suparta, Mundzier (ISLAMICA: Jurnal Studi Keislaman, 2013)
The basic argument that this paper tries to prove is that, education can be counter-productive to the most important value of humanity if it is run inappropriately. Given that value can be producedâin this modern timeâby telecommunication and information technology, education cannot turn a blind eye on it. By implication, education cannot ignore modernity. It is this problem that this paper is concerned with. The paper is interested in discussing the idea of transformative education by relating it to many sources and factors of transformation. Modernity is certainly one of those. The paperâborrowing UNESCOâunderstands education as simply the learning to know, the learning to do, to be, and to live together. Consequently, education is all about adapting oneself to the environment in which he/she lives. It is in this context that education cannot escape modernity, for modernity has become the very part of human life and environment. And it is only through modernityâthis paper arguesâthat education can be meaningful at least in democratic terms.